Evaluasi Formulasi Sediaan Floating Mikroenkapsulasi yang Mengandung Ekstrak Etanol Daun Pepaya (Carica Papaya L.) - Glory Stevi Natasia Saragih; Razoki Razoki; Muhammad Yunus; Hariyadi Dharmawan Syahputra (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Microencapsulation is a technology that uses controlled release of active ingredients to increase bioavailability and reduce gastrointestinal irritation. This study aims to evaluate the microencapsulation formulation of ethanol extract of papaya leaf (Carica papaya L.) by testing its stability, moisture content, and floating in the stomach and intestinal medium. Mardikasari et al (2020) showed the release of chitosan-alginate microencapsulation of 8,811 mg/L (acid) and 79,908 mg/L (base). Microencapsulation was performed by adding sodium alginate and chitosan as polymers, CaCl2 as a cross-linking, and three variations of extract concentration in F1 without extract, F2 of 0,25%, F3 of 0,5%, and F4 of 0,75%. The results showed that all formulas remained stable during the storage cycle in terms of color, aroma, taste, and texture. The average moisture content of the microencapsulated formulations was 24%, 20,5%, 28%, and 18,7%. The microencapsulated preparations were able to maintain their stability in the acidic conditions in the stomach, but showed a decrease in floating under acidic conditions in the intestine.